2021
DOI: 10.1038/s41598-020-79437-1
|View full text |Cite
|
Sign up to set email alerts
|

An experimental pig model with outer retinal degeneration induced by temporary intravitreal loading of N-methyl-N-nitrosourea during vitrectomy

Abstract: We aimed to develop an outer retinal degeneration pig model induced by temporary intravitreal loading of N-methyl-N-nitrosourea (MNU) during vitrectomy. In a preliminary experiment involving 5 mini-pig cases to determine the appropriate concentration of MNU, the vitreous cavity of each eye was filled with 4, 8, 10, 12, or 16 mg/mL MNU for 10 min, which was then replaced with a balanced salt solution. Multimodal examinations including spectral-domain optical coherence tomography (OCT) images and full-field elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…We previously showed that our new RD model could be successfully induced with MNU in a larger animal 28 . In that study, the results were evaluated by multimodal examinations, including spectral-domain optical coherence tomography (OCT) imaging, ffERG recording, and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…We previously showed that our new RD model could be successfully induced with MNU in a larger animal 28 . In that study, the results were evaluated by multimodal examinations, including spectral-domain optical coherence tomography (OCT) imaging, ffERG recording, and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 89%
“…Although the degeneration process observed in the MNU-treated model was similar to that of genetically induced ones, there were differences in the distribution of degeneration in the retina. Unlike genetically induced RD, which causes global homogeneous expression of RD throughout the retina, MNU-treated RD exhibited local heterogeneities in RD expression even when MNU was spread evenly throughout the retina 28 , 34 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations